ASSESSMENT OF THE IMPACTS OF LAND USE ON WATER QUALITY OF BRANTAS UPSTREAM , BATU CITY, INDONESIA - Bambang Rahadi Widiatmono; Fajri Anugroho; Euis Elih Nurlaelih; Akhmad Adi Sulianto; Novia Lusiana (Journal of Environmental Engineering and Sustainable Technology, 2017)
Unsuitability land uses have significant impact on conditions of many river basins along line from upstream to downstream  through the cities in Indonesia. Water of Brantas upstream running along line through Batu City from Bumiaji Sub-District to Junrejo Sub-District may show varied concentrations of contaminants. The objective studies are (i) to evaluate the land use at existing-condition; (ii) to monitor the water quality parameters; (iii) to assess the water quality index and water pollution index of the Brantas upstream water. In this study, Pearson correlation of BOD and COD  shown a very high positive correlations (r) of 0.8779. Meanwhile, high positive correlations were shown in TSS vs T-PO4 and T-NO3 vs T-PO4, whereas DO vs TDS, DO vs T-NO3, and DO vs T-PO4 have high negative correlations. Based on the four river water quality classifications in Indonesia, all stations shown the status of water pollution index at moderate level (Class I and II). Meanwhile, the water pollution index status of Class III were dominated by moderate level. In contrast, the status of water pollution index in Class IV was dominated by good level. Water pollution index in Category IV was relatively similar result to NSF-WQI status rather than other categories.Keyword: Brantas upstream watershed, land use, water pollution index, water quality parameters